Revisiting the influence of regulatory focus on eagerness and vigilance in signal detection. Issue 3 (1st September 2020) - Krishna, Anand
ABSTRACT: A core prediction of classical regulatory focus theory is that a promotion focus should bias responses towards more hits in a signal detection task and a prevention focus towards more correct rejections. However, it is unclear whether this is also true when rejection is enacted by inhibiting a response. Three initial pre-registered studies show that regulatory focus does not bias response patterns in a speeded go/nogo signal detection task in which the absence of a signal requires inhibition, over two manipulations of regulatory focus and two different signal-to-noise ratios. A further registered study shows that while the predicted effect does occur in a word recognition task modelled on previous research, it is obviated by the presence of time pressure when responding. Though these findings cannot definitively answer whether regulatory focus effects generalize to response inhibition, they highlight the importance of cognitive elaboration time for regulatory focus effects and provide important insight towards understanding their operating conditions. In addition, surprising results from a registered pilot study show that regulatory focus manipulations on the tactical level may have unpredictable results, providing methodological recommendations for future research.